Safflower Yellow and Its Main Component HSYA Alleviate Diet-Induced Obesity in Mice: Possible Involvement of the Increased Antioxidant Enzymes in Liver and Adipose Tissue - Yan, Kemin; Wang, Xin; Pan, Hui; Wang, Linjie; Yang, Hongbo; Liu, Meijuan; Zhu, Huijuan; Gong, Fengying (Frontiers in Pharmacology, 2020)
Purpose: Oxidative stress plays an important role in the pathogenesis of obesity and its associated disorders. Safflower yellow (SY) and hydroxysafflor yellow A (HSYA), the natural compounds isolated from Carthamus tinctorius L., has been found to possess antioxidative and anti-obesity properties. The purpose of the present study is to investigate whether SY and its main component HSYA alleviate obesity by the antioxidant effects. Methods: Diet-induced obese (DIO) mice were treated with 200 mg/kg/d SY or HSYA for ten weeks. Body weight, fat mass, serum biochemical parameters and superoxide dismutase (SOD) activities were measured. Glucose and insulin tolerance tests were performed. The expression of antioxidant enzymes in liver and adipose tissue were measured. In vitro, H2O2-induced oxidative stress HepG2 cells and 3T3-L1 adipocytes were treated with SY and HSYA to investigate the direct effects of SY and HSYA on the expression of antioxidant enzymes. Results: SY and HSYA significantly decreased the body weight gain of DIO mice, and decreased fat mass to 57.8% and 61.6% of the control mice, respectively (P＜0.05). The parameters of glucose metabolism and liver function were improved after SY and HSYA treatment. The hepatic SOD activities and the mRNA levels of antioxidant enzymes in liver and adipose tissue of SY and HSYA treated mice were increased (P＜0.05). Meanwhile, the administration of SY and HSYA on the H2O2-induced oxidative stress HepG2 cells and adipocytes also increased the expression of the antioxidant factor and antioxidant enzymes to 1.2~3.3 folds of the control cells (P＜0.05). Conclusion: SY and its main component HSYA could significantly decrease the fat mass, and improve glucose metabolism and liver function in diet-induced obese mice. The beneficial effects of SY and HSYA on obesity and metabolism may be associated with the increased expression of antioxidant enzymes in liver and adipose tissue.